PENGARUH FASILITAS BELAJAR SEKOLAH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMAN 19 PEKANBARU - Camila, Maudhi Nur; Haryana, Gani; Isjoni, M. Yogi Riyantama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of school learning facilities on students’ learning outcomes in Economics subject at SMA Negeri 19 Pekanbaru. The background of the research is based on the condition of school learning facilities that are still limited and in the development stage, which is suspected to affect learning outcomes, as indicated by the fact that some students have not yet reached the Minimum Mastery Criteria. The sample consisted of 193 students from grades X and XI, selected using proportionate stratified random sampling. Data were collected through documentation and questionnaires, then analyzed using descriptive analysis and simple linear regression. The results of the study indicate that school learning facilities have a positive and significant effect on students’ learning outcomes, as evidenced by the t-test which showed a significance value of 0.00 (< 0.05) and a t-count value of 8.112 greater than the t-table value of 1.972, indicating that the research hypothesis is accepted. The coefficient of determination shows that school learning facilities contribute 25.6% to the improvement of learning outcomes. Thus, it can be concluded that the influence of school learning facilities on learning outcomes is significant in this study.